2014
DOI: 10.1007/s11033-014-3786-1
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 expression and IL10 promoter polymorphism in acute myeloid leukemia with RUNX1-RUNX1T1

Abstract: We investigated the correlation between FLT3 expression and IL10 gene promoter polymorphism in acute myeloid leukemia with RUNX1-RUNX1T1 and their clinical significance. FLT3 mRNA expression was measured by real-time quantitative PCR (qPCR) and immunohistochemical staining (IHC) on bone marrow (BM) leukemic cells. IL10 gene promoter polymorphisms including rs1800896 (G-1082A), rs1800871 (C-819T), and rs1800872 (C-592T) were genotyped by direct sequencing. Among 45 enrolled patients, 32 (71.1 %) exhibited FLT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…In contradiction, Kim et al reported a lower OS (estimated 20.1 months) in case of the GA variant genotype compared to GG homozygous genotype (estimated 54.6 months) for the IL-10 rs1800896 SNP in AML patients. 36 Similar to our findings, Kim et al, revealed that the IL-10 rs1800871 and rs1800872 variant genotypes did not have an effect on OS. 36 Similar results regarding this lack of effect on OS by IL-10 rs1800871 have been previously reported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contradiction, Kim et al reported a lower OS (estimated 20.1 months) in case of the GA variant genotype compared to GG homozygous genotype (estimated 54.6 months) for the IL-10 rs1800896 SNP in AML patients. 36 Similar to our findings, Kim et al, revealed that the IL-10 rs1800871 and rs1800872 variant genotypes did not have an effect on OS. 36 Similar results regarding this lack of effect on OS by IL-10 rs1800871 have been previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…36 Similar to our findings, Kim et al, revealed that the IL-10 rs1800871 and rs1800872 variant genotypes did not have an effect on OS. 36 Similar results regarding this lack of effect on OS by IL-10 rs1800871 have been previously reported. 37 Pehlivan et al found no association between TNF-α rs1800629, IL-10 rs1800872, rs1800871, and rs1800896, IFN-γ rs2430561, and TGF-β1 rs1800470 (codons 10 and 25) polymorphisms and OS in their Turkish CML patients, 13 being therefore in line with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The c-KIT mutation has been proven to cooperate with the AML1-ETO fusion to induce leukemia (3,5). Still there are other gene mutations, including WT1, FLT3-ITD and PDGFR mutations, that have been reported to be involved in the progression of this subtype of leukemia (68), further supporting an oncogenic cooperation in leukemogenesis between RUNX1-RUNX1T1 and additional molecular alterations. Therefore, detailed detection of the gene mutation profile at diagnosis and relapse could deepen the understanding of leukemia development and progression.…”
Section: Introductionmentioning
confidence: 96%
“…This might be related to the formation of RUNX1-RUNX1T1 producing multiple proteins in the nucleus and cytoplasm [ 28 , 29 ]. Some mutations, such as FLT3 mutations [ 30 ] and miRNA overexpression [ 31 ], also affect the prognoses of RUNX1-RUNX1T1 positive patients. There are about 25% of patients with t(8;21) or positive RUNX1-RUNX1T1 fusion gene that also has c- KIT mutations, changing the prognosis from good to moderate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%